Recovery of Campylobacter from feed using different enrichment media. Issue 9 (11th October 2021) - Richardson, K. E.; Cox, N. A.; Berrang, M. E.; Powell, A.; Weller, Cheryl
Abstract: Studies were conducted to investigate the recovery of Campylobacter from feed. The impact of feed moisture, water activity, pH, number of background microflora and the use of different antibiotic supplements in Campylobacter enrichment broth (CEB) on Campylobacter recovery were evaluated in five studies. Broiler starter feed was inoculated with 10 4 −10 5 cfu of Campylobacter /g and stored at 24 °C and 43% RH. Enrichment culture was conducted on the day of inoculation or 24 h post inoculation and every 48 h of storage thereafter for 14 d. Feed moisture, water activity, pH and level of background microflora were not correlated with Campylobacter recovery. The incubation of feed in CEB with no antibiotic supplement resulted in the number of background microflora increasing to 10 9 cfu/g and the pH of the media decreasing to pH 4-5 impacting recovery. Addition of certain antimicrobial supplements to CEB reduced background microflora growth and maintained a near neutral pH. Campylobacter was recovered up to 10 days post inoculation when using CEB containing antibiotic supplements compared to 1 day in CEB. These findings suggest that Campylobacter can be recovered from feed and the type of antimicrobial supplement utilized influences recovery by controlling extraneous microbial growth which occurs during enrichment.